THEORETICAL APPROCH OF THE LIGAND COORDINATION IN Ln(tBuNC(CH3)NtBu)3 Ln = Y, La, Lu - Bouchekioua, S; Ouddai, N (university of el oued/جامعة الوادي, 2018)
The theoretical study carried by the quantum DFT method on the coordination mode of ligand amidinate to lanthanide in the series Ln(tBuNC(CH3)NtBu)3 where Ln = Y, La, and Lu, showed interesting results. A distorted trigonal prismatic structure (θ = 30°) is obtained. The lanthanide-amidinate bond has a covalent contribution (20%), confirmed by the presence of molecular orbitals metal and nitrogen character. These two results with those found in previous works; gave a correlation between the covalent percentage of the bond and the geometric distortion θ. The quantum descriptors of the conceptual DFT describe the compounds studied as weak electrophiles (μ = 0.9eV). From our theoretical analysis emerge a good candidate for heterogeneous catalysis.
Article
Keywords: DFT; lanthanides; amidinates; torsion angle; BDE